Exploring the pathogenesis of severe acute respiratory syndrome (SARS): the tissue distribution of the coronavirus (SARS‐CoV) and its putative receptor, angiotensin‐converting enzyme 2 (ACE2) - To, KF (J Pathol, 2004)
Severe acute respiratory syndrome (SARS) is an emerging infectious disease associated with a new coronavirus, SARS‐CoV. Pulmonary involvement is the dominant clinical feature but extra‐pulmonary manifestations are also common. Factors that account for the wide spectrum of organ system involvement and disease severity are poorly understood and the pathogenesis of SARS‐CoV infection remains unclear. Angiotensin converting enzyme 2 (ACE2) has recently been identified as the functional cellular receptor for SARS‐CoV. Studies of the tissue and cellular distribution of SARS‐CoV, and ACE2 protein expression, reveal new insights into the pathogenesis of this deadly disease. ACE2 is expressed at high level in the primary target cells of SARS‐CoV, namely pneumocytes and surface enterocytes of the small intestine. Despite the fact that SARS‐CoV can infect the lung and intestine, the tissue responses in these two organs are different. All other tissues and cell types expressing ACE2 may be potential targets of SARS‐CoV infection. Remarkably, endothelial cells, which express ACE2 to a high level, have not been shown to be infected by SARS‐CoV. There is also evidence that cell types without detectable ACE2 expression may also be infected by the virus. Furthermore, studies in a new human cell culture model have indicated that the presence of ACE2 alone is not sufficient for maintaining viral infection. Therefore, other virus receptors or co‐receptors may be required in different tissues. Moreover, the interaction between SARS‐CoV and the immunological or lymphoid system remains to be defined. It is clear that we are only at the dawn of our understanding of the pathogenesis of SARS. As our knowledge of the pathogenic mechanisms improves, a more rational approach to therapeutic and vaccine development can be designed in order to combat this new and fatal human disease. Copyright © 2004 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.